Evolutionary thinking in medicine from research to policy and practice - Alvergne, Alexandra; Jenkinson, Crispin 1962-; Faurie, Charlotte (Advances in the evolutionary analysis of human behaviour, 2016)
The aim of this edited book is to provide health professionals, across a wide variety of specialisms, with a targeted access to evolutionary medicine. Throughout the book, the views of both medical and evolutionary scientists on the latest relevant research is presented with a focus on practical implications. The inclusion of boxes explaining the theoretical background as well as both a glossary for technical terms and a lay summary for non- specialists enable medical researchers, public health professionals, policy makers, physicians, students, scholars and the public alike to quickly and easily access appropriate information. This edited volume is thus relevant to anyone keen on finding out how evolutionary medicine can improve the health and well-being of people.